Euskal artikuluak bultza ditzakeen interpretazioez - Etxeberria, Urtzi (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
This paper proposes a novel analysis for the Basque definite determiner [-a] where it is argued, in opposition to other scholars (cf. Artiagoitia 2002, 2006 where [-a] is argued to be a number marker when it gets the existential narrow scope interpretation), that the Basque definite determiner (despite its various interpretations) is just that, a definite determiner. Moreover, based on the behaviour of this element, this paper provides extra evidence in favour of the Neocarlsonian approach (cf. Chierchia 1998b, Dayal 2004) where the existential interpretation of bare nouns (BN) is shown to be dependent on the kind-level reading. This evidence should also be taken as proof against the so-called Ambiguity analysis (cf. Diesing 1992, Kratzer 1995, a.o.) or the property-based approach to BNs (cf. McNally 1995, Laca 1996, Dobrovie-Sorin & Laca 2003) where BNs' existential interpretation is argued to be non-dependent on any other reading. Furthermore, observing the different interpretations that the D can force in Basque —referential, kind, and existential—, this language is shown to be typologically in between English and French (as argued by Etxeberria 2005, 2007).